Racial and Ethnic Differences in Acute Coronary Syndrome and Myocardial Infarction Within the United States: From Demographics to Outcomes. Issue 5 (30th March 2016) - Graham, Garth
ABSTRACT: In the United States, different races, ethnicities, and their subgroups experience disparities regarding acute coronary syndrome (ACS) and myocardial infarction (MI). This review highlights these differences across 4 stages that comprise the ACS/MI narrative: (1) patient demographics, (2) patient comorbidities and health risks, (3) treatments and their delays, and (4) outcomes. Overall, black and Hispanic ACS/MI patients are more likely to present with comorbidities, experience longer delays before treatment, and suffer worse outcomes when compared with non‐Hispanic white patients. More specifically, across the studies analyzed, black and Hispanic ACS/MI patients were consistently more likely to be younger or female, or to have hypertension or diabetes, than non‐Hispanic white patients. ACS/MI disparities also exist among Asian populations, and these are briefly outlined. However, black, Hispanic, and non‐Hispanic white ACS/MI patients were the 3 most‐studied racial and ethnic groups, indicating that additional studies of other minority groups, such as Native Americans, Asian populations, and black and Hispanic subgroups, are needed for their utility in reducing disparities. Despite notable improvement in ACS/MI treatment quality measures over recent decades, disparities persist. Causes are complex and extend beyond the healthcare system to culture and patients' personal characteristics; sophisticated solutions will be required. Continued research has the potential to further reduce or eliminate disparities in the comorbidities, delays, and treatments surrounding ACS and MI, extending healthy lifespans of many underserved and minority populations, while reducing healthcare costs.